Finance and Development, June 2002. (Finance and Development; Finance and Development ;, 2002)
This paper highlights that despite unprecedented gains in living standards in some countries over the past few decades, poverty continues as a harsh reality in too much of the developing world. The causes lie in part with poor country governments that have not followed through on the policies and programs needed to accelerate growth and eradicate poverty. But they also reflect the uneven record of development assistance and protectionist trade policies and agricultural subsidies in industrial countries, which have dampened profitable investment and growth in the developing world.